War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Interrogating Evil in Videogames about Violent Conflicts - Hammar, Emil Lundedal; Pötzsch, Holger (The Routledge International Handbook of Perpetrator Studies, 2020)
This contribution interrogates the figure of the perpetrator as it emerges in narrative videogames. First, we provide a brief outlook on some key characteristics of videogames, before we discuss how the specific affordances of this “new” medium offer unprecedented ways of approaching and dealing with perpetrators and perpetration. Finally, we offer concrete examples from three games to illustrate different possible configurations of the playerperpetrator nexus—Yager Development’s Spec Ops: The Line (2012), 11 Bit Studio’s This War of Mine (2015), and Hangar 13’s Mafia III (2016). In contrast to other media, games enable an active exploration of, and participation in, a variety of possible offenses. Rather than merely witnessing evil deeds, players are immersed in simulated environments that demand constant evaluations of complex settings and require decision-making under systemic limitations. This performative aspect of play makes games a unique medium for learning and teaching about the intricate logics and innate dynamics of perpetrations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé